A DYNAMIC APPROACH TO THE START-UP BUSINESS ECOSYSTEM: A CROSS-COMPARISON OF KOREA, CHINA, AND JAPAN - Myungho Lee; Minhwa Lee; Junic Kim (Asian Academy of Management Journal, 2017)
This study aims to explore in detail the business ecosystems for high-tech start-ups in Korea, China, and Japan using a dynamic approach. For this purpose, this study proposes the start-up life cycle (SLC) framework, which includes the stages of technology optimisation (R&D), fundraising, and exit, which is based on overcoming obstacles at each developmental stage, such as the Valley of Death and Darwinian Sea, the two major startup business barriers. Thus, this study enables accounting for the macroscopic dynamic flow and quantitative comparison of the business ecosystem. Each country shows very different start-up business ecosystem characteristics: Korea has a supply-centric ecosystem, whereas Japan and China have a technology-centric and a market-centric ecosystem, respectively. The analysis performed in this study enables us to recognise the significant differences between the technology start-up ecosystems in the three countries. Furthermore, the SLC framework suggested in this study not only allows for an analysis of the critical path of the entrepreneur and the capital in the start-up business ecosystem but also permits an understanding of the characteristics of the start-up business ecosystem of each country through radial graphs. This study dynamically contributes to the understanding of the entire start-up business ecosystem in each country and enables an understanding of the direction of future start-up policies by comparing the three different ecosystems.